Traditional Institutions in Modern Times: Dowries as Pensions When Sons Migrate - Natalie Bau; Gaurav Khanna; Corinne Low; Alessandra Voena (The Quarterly Journal of Economics, 2026)
Abstract This paper uses newly collected data on the allocation of dowry to examine its role in resolving intergenerational frictions around migration in India. Migration disrupts traditional elderly support structures, in which sons live near their parents and care for them in old age. We develop a model in which dowry can promote migration by allowing sons to make upfront transfers to their parents and ease constraints on income sharing. To test this hypothesis, we collect two new data sets that measure the distribution of dowry between family members. We document for the first time that net transfers of dowry to a man’s parents are common but far from universal. Consistent with using dowry for income sharing, such transfers occur more often when sons migrate, especially when they work in higher-earning occupations. In nationally representative data, migration rates are higher in areas with stronger historical dowry traditions. Finally, exploiting a large-scale highway construction program, we show that men from areas with stronger historical dowry traditions migrate more when migration costs fall. Our findings provide some clues as to why dowry persists despite its well-documented adverse consequences.